KOMITMEN ORGANISASIONAL PADA PERUSAHAAN EXPRESS DI JAKARTA - KAREL TJAHJADI; IVAN KURNIA (Media Bisnis, 2019)
This study examined the influence of transformational leadership, motivation, and job satisfaction of organizational commitment of PT.Global JET Express. This study involve 100 respondents as a sample, all of them are permanent employees of PT. Global JET Express. The number of respondents was determined using the nonprobability sampling technique, by purposive sampling method. Multiple regression is used as a data analysis technique and processed using SPSS 25 program. The results showed that motivation had a positive and significant effect on organizational commitment, while of transformational leadership and job satisfaction has no effect on job satisfaction. Based on the results of the analysis obtained in this study, the management of PT. Global JET Express is expected to pays more attention to motivation experienced by employees, so that the level of organizational commitment felt by employees can increase.